Trichomonas vaginalis Prevalence and Correlates in Women and Men Attending STI Clinics in Western Canada. Issue 10 (October 2017) - Gratrix, Jennifer; Plitt, Sabrina; Turnbull, LeeAnn; Smyczek, Petra; Brandley, Judith; Scarrott, Ron; Naidu, Prenilla; Bertholet, Lindsay; Chernesky, Max; Read, Ron; Singh, Ameeta E.
Abstract : Abstract: Trichomonas vaginalis prevalence (2.8%) in female sexually transmitted infection clinic attendees was within the prevalence of chlamydia (5.8%) and gonorrhea (1.8%), while being very low for male attendees (0.2%). Correlates among women were indigenous ethnicity, other ethnicity, and being symptomatic. Abstract : Trichomonas vaginalis prevalence (2.8%) in female Canadian sexually transmitted infection clinic attendees was within the prevalence of chlamydia (5.8%) and gonorrhea (1.8%), while being very low for male attendees (0.2%).